PRACTICE OF DETERMINING THE PRICE OF PALM FRUIT BUNCHES BY PT HARI SAWIT JAYA SUMATERA UTARA FROM THE PERSPECTIVE OF SHARIA ECONOMIC LAW - Liza Zahara Br Hasibuan; Anggie Yolanda Ritonga (JURISTA: Jurnal Hukum dan Keadilan, 2026)
This article examines the practice of determining the price of fresh fruit bunches (FFB) of oil palm by PT Hari Sawit Jaya in North Sumatra from the perspective of Islamic economic law. This article uses an empirical juridical method with data obtained through interviews, participant observation, and documentation to explore the pricing mechanism and farmer involvement. The results of the study show that the pricing determined by PT Hari Sawit Jaya is often non-transparent and unilateral, without involving partner farmers, thereby causing injustice and economic losses for farmers. This practice contradicts the principles of Islamic economic law, which emphasises fairness, openness, and mutual agreement without uncertainty (gharar) and injustice (zulm). Although the company attempts to adjust prices to market conditions, the absence of transparent and participatory mechanisms leaves farmers in a weak bargaining position. This study also highlights the importance of the government's role in supervising and facilitating price setting in accordance with regulations and sharia principles in order to create fair and sustainable partnerships. In conclusion, the pricing of FFB at PT Hari Sawit Jaya needs to be reformed by increasing transparency, fairness, and farmer participation in accordance with sharia economic principles to strengthen farmer welfare and the stability of the palm oil industry. These findings are important as a reference for public policies that support the sustainability of the palm oil plantation sector in Indonesia.